(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In the 21st century, education has undergone significant transformations due to rapid technological advancements, globalization, and changing learning needs. Traditional teaching methods are no longer sufficient to prepare students for the complexities of modern life. This paper explores effective teaching strategies, including active learning, technology integration, differentiated instruction, collaborative learning, and student-centered approaches. By implementing these strategies, educators can enhance student engagement, critical thinking, and problem-solving skills, preparing them for lifelong learning.